Menkes disease--an autopsy case with metal analysis of hair. - Moon, H. R. (Korean Academy of Medical Sciences, 1987)
We report the first case of Menkes' disease in Korea, occurring in a 1 1/2 year old boy with characteristic clinical, arteriographic and pathologic features. Postmortem examination revealed widespread neuronal destruction and abnormally tortuous and elongated large arteries including cerebral, visceral and limb vessels. Microscopically, many of the hairs formed were twisted (pili torti), of varying caliber (monilethrix), and fractured (trichorrhexis nodosa). In the radioactivated analysis of scalp hair, copper elements was not found. The abnormal vessels were characterized by fragmentation and disruption of the internal elastic lamina with intimal proliferation. The neuronal destruction was widespread in the cerebral gray matter and in the cerebellum, and there was associated gliosis. The changes in the cerebellum were particularly severe, with neuronal loss in the internal granular cell layer. Many Purkinje cells were lost, and the remainder showed unusual dendritic sprouts from the cell body and grotesque proliferation of dendritic tree. In other organs, mild chronic peribronchitis, and scattered foci of immature glomeruli in renal cortex were noted.